Mediators and theories of change in psychotherapy with adolescents: a systematic review protocol - Taubner, Svenja; Saliba, Andrea; Heinonen, Erkki; Protić, Sonja; Volkert, Jana; Adler, Asta; Barkauskiene, Rasa; Cerón, Sonia Conejo; Giacomo, Dina Di; Ioannou, Yianna; Mestre, Jose M.; Moreno-Peral, Patricia; et al. (BMJ open, 2021)
Introduction Approximately 75% of mental disorders emerge before the age of 25 years but less than half receive appropriate treatment. Little is known about the mechanisms underlying the therapeutic change of adolescents in psychotherapy. The ‘European Network of Individualised Psychotherapy Treatment of Young People with Mental Disorders’, funded by the European Cooperation in Science and Technology, will conduct the first systematic review to summarise the existing knowledge on mediators and theories of change in psychotherapy for adolescents. - Method A systematic review will be conducted, conforming to the reporting guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement recommendations. Electronic databases (PubMed and PsycINFO) have been systematically searched on 23 February 2020, for prospective, longitudinal and case-control designs which examine mediators of change. Participants will be adolescents between 10 and 19 years of age who suffer from a mental disorder or psychological difficulties and receive an intervention that aims at preventing, ameliorating and/or treating psychological problems. - Ethics and dissemination Ethical approval is not required for this systematic review as no primary data will be collected. The results will be published in a peer-reviewed journals and at conference presentations and will be shared with stakeholder groups. The whole data set will be offered to other research groups following recommendations of the open science initiative. Databases with the systematic search will be made openly available following open science initiatives. - PROSPERO registration number CRD42020177535.